Optimizing Digital Marketing Strategy for Small and Medium Enterprises in North Sulawesi - Munaiseche, Maya; Mandey, Nancy Henrietta Jessamine; Rooroh, Betsy; Ponggawa, Venny; Lumunon, Edwin (MEC-J (Management and Economics Journal), 2025)
This study aims to identify internal and external factors of MSMEs related to digital marketing and formulate strategies and recommendations so that the use of digital marketing is optimal and has good competitiveness in local, national, and global markets. To achieve this goal, a quantitative method is used; the population of this study is MSME actors who are considered to understand external and internal factors and are involved in forming their business strategies. Samples were collected by purposive sampling, namely MSMEs who plan or are using digital marketing for their marketing activities; with the Slovin formula, 397 respondents were obtained, but only 62% could be used (250). Using the SWOT analysis tool, the results of the study were obtained: IFA scored 3.95, and EFA scored 3.89. Based on QSPM, 14 strategies were obtained according to their respective priority orders, and the top 3 strategies were: utilizing e-commerce platforms, increasing marketing activities, and maximizing personal content. Implementing these priority activities will allow MSMEs to adapt to the digital ecosystem quickly. The implication is that MSMEs need to be given technical training and assistance in using digital platforms, such as creating online stores, managing transactions, conducting promotions, or analyzing data available on social media. Theoretical implications support the theory that MSME growth in the digital landscape requires more effective offensive and proactive strategies. This provides an opportunity for further research to explore the use of digital marketing in MSMEs more deeply.